A produção de cuidado nos centros de atenção psicossocial na perspectiva dos trabalhadores de saúde mental - Assini, Luciana Nazareth Guedes Alcoforado (2022)
This study aims to understand, from the theoretical framework of psychosocial care, the production of mental health care in Psychosocial Care Centers (CAPS) in the metropolitan region of Vitória, ES, from the perspective of mental health professionals. A strategic device of the current public policy on mental health care, the CAPS is a territorially based, community-based service that constitutes one of the assistance and care points that make up the Psychosocial Care Network - RAPS. Psychosocial Care is considered as a field formed from diverse practices that dialogue with different cores of knowledge and theories, which are added to formulate interventions, policies, bets and different ways of leading life. This is a research with a qualitative approach, using focus groups for data collection, with mental health professionals from different backgrounds, CAPS workers, as participants. The focus groups were carried out in two moments: the first moment seeking an initial approach and familiarization with the theme and the second, carried out through the presentation of the preliminary analysis of the first meeting of the group and directed to the deepening of the theme. The focus group sessions were transcribed and analyzed using the IRaMuTeQ software (Interface de R pour les Analyzes Multidimensionnelles de Textes et de Questionnaires). The categories were determined through the lexical classes obtained from the analyzes and received the following nominations: 1. The dynamics of care - a theoretical-practical process; 2. Limits, possibilities and challenges of networked care. The results pointed to the questioning between the care recommended from the paradigm of psychosocial care and what is effectively carried out in the reality of the services. Despite the anguish generated by the difficulties in the daily life of the services, there is a commitment to support attention and care for the person in psychological distress within the anti- asylum premises. In the work process, they attribute to the team a place of tension and exhaustion, at the same time as a possibility of sharing, mutual support and a fundamental role in the composition of the psychosocial care mode. The results brought elements about the specificity of work at CAPS in crisis management, in promoting access and autonomous use of medication, in territorial actions in the search for social inclusion of users. With regard to the relationship between the CAPS and other points of care and management, the results point to the difficulty of interlocution between this service both with higher management and with other points in the network, denouncing gaps that compromise psychosocial care. However, the participants defend the CAPS as a place of power in this care, standing out in relation to other equipment.